Efficient detection of RNA–protein interactions using tethered RNAs - Iioka, Hidekazu (Oxford University Press, 2011)
The diverse localization of transcripts in cells suggests that there are many specific RNA–protein interactions that have yet to be identified. Progress has been limited, however, by the lack of a robust method to detect and isolate the RNA-binding proteins. Here we describe the use of an RNA aptamer, scaffolded to a tRNA, to create an affinity matrix that efficiently pulls down transcript-specific RNA-binding proteins from cell lysates. The addition of the tRNA scaffold to a Streptavidin aptamer (tRSA) increased binding efficiency by ∼10-fold. The tRSA system with an attached G-quartet sequence also could efficiently and specifically capture endogenous Fragile X Mental Retardation Protein (FMRP), which recognizes this RNA sequence. An alternative method, using biotinylated RNA, captured FMRP less efficiently than did our tRSA method. Finally we demonstrate the identification of novel RNA-binding proteins that interact with intron2 or 3′-UTR of the polarity protein Crumbs3 transcript. Proteins captured by these RNA sequences attached to the tRNA scaffold were identified by mass spectrometry. GFP-tagged versions of these proteins also showed specific interaction with either the Crb3 intron2 or 3′-UTR. Our tRSA technique should find wide application in mapping the RNA–protein interactome.